2006
DOI: 10.1001/archneur.63.3.345
|View full text |Cite
|
Sign up to set email alerts
|

An Observational Study of Cognitive Impairment in Amyotrophic Lateral Sclerosis

Abstract: Background: Cognitive impairment is increasingly recognized in patients with amyotrophic lateral sclerosis (ALS). Clinical and pathologic features overlap in frontotemporal lobar dementia and ALS. Demographics, respiratory status, bulbar site of onset, and disease severity are potential risk factors for cognitive impairment in ALS. Objectives: To further delineate the frequency, nature, and implications of cognitive impairment in ALS and to assess previously identified risk factors. Design: Case-control and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
81
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 138 publications
(92 citation statements)
references
References 42 publications
9
81
2
Order By: Relevance
“…This is consistent with some previous studies [56,57] but contrary to other studies [35,58]. In our study, stereotypical behaviour, apathy, and disinhibition do not predict the survival of ALS patients, which is consistent with one previous study using the same scale [59].…”
Section: Accepted Manuscriptsupporting
confidence: 91%
See 4 more Smart Citations
“…This is consistent with some previous studies [56,57] but contrary to other studies [35,58]. In our study, stereotypical behaviour, apathy, and disinhibition do not predict the survival of ALS patients, which is consistent with one previous study using the same scale [59].…”
Section: Accepted Manuscriptsupporting
confidence: 91%
“…Previously, some studies have found that people with bulbar onset of ALS are more likely to have cognitive impairment than those with spinal onset [39,53,54], but others do not [33,35,55]. In our study, the site of onset had no effect of the presence of cognitive impairment as determined by the ACE-III, but site of onset influenced cognitive impairment based on FAB logistic regression results.…”
Section: Accepted Manuscriptcontrasting
confidence: 58%
See 3 more Smart Citations